A history of charisma. - Potts, John 1959- (Basingstoke Palgrave Macmillan, 2009)
This text traces the history of the word 'charisma', and the various meanings assigned to it, from its first century origins in Christian theology to its manifestations in 21st century politics and culture, while considering how much of the word's original religious meaning persists in the contemporary secular understanding.
Keywords: Charisma (Personality trait) -- History; English language -- Etymology; English language -- History; English language -- Word formation; Pentecostalism -- History